Planets in Binary Star Systems - Haghighipour, Nader (Astrophysics and Space Science Library,, 2010)
The discovery of extrasolar planets over the past decade has had major impacts on our understanding of the formation and dynamical evolution of planetary systems. There are features and characteristics unseen in our solar system and unexplainable by the current theories of planet formation and dynamics. Among these new surprises is the discovery of planets in binary and multiple-star systems. The discovery of such "binary-planetary" systems has confronted astrodynamicists with many new challenges, and has led them to re-examine the theories of planet formation and dynamics. Among these challenges are: How are planets formed in binary star systems? What would be the notion of habitability in such systems? Under what conditions can binary star systems have habitable planets? How will volatiles necessary for life appear on such planets? This volume seeks to gather the current research in the area of planets in binary and multistar systems and to familiarize readers with its associated theoretical and observational challenges.